2018
DOI: 10.3892/mmr.2018.8383
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of bidirectional effect of arsenic on ERK signaling pathway

Abstract: Arsenic is a toxic metal, which ultimately leads to cell apoptosis. ERK is considered a key transcriptional regulator of arsenic-induced apoptosis. Due to a few controversial issues about arsenic-mediated extracellular signal-regulated MAP kinases (ERK) signaling, a meta-analysis was performed. Subgroup analyses demonstrated that high doses (≥2 µmol/l) of arsenic increased the expression of Ras, ERK, ERK1, ERK2, phosphorylated (p)-ERK, p-ERK1, and p-ERK2, while low doses (<2 µmol/l) decreased the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…ERK is an important member of the mitogen-activated protein kinase (MAPK) family and plays an important role in regulating different biological processes in different cells, including proliferation, differentiation, survival and apoptosis (16). The results of the present study indicated that the activation of the ERK signaling pathway exerted anti-apoptotic ERK protein may be a regulatory target for miR-302d-3p.…”
Section: Discussionmentioning
confidence: 58%
“…ERK is an important member of the mitogen-activated protein kinase (MAPK) family and plays an important role in regulating different biological processes in different cells, including proliferation, differentiation, survival and apoptosis (16). The results of the present study indicated that the activation of the ERK signaling pathway exerted anti-apoptotic ERK protein may be a regulatory target for miR-302d-3p.…”
Section: Discussionmentioning
confidence: 58%
“…The metal-activated mediators leading to ERK1/2 phosphorylation can be cell-specific and dose-dependent: at 1 mM, W activated the BKαβ1 channels and ERK1/2 phosphorylation in HEK cells [105], but at 30 nM it had no effect on BKαβ1-mediated ERK1/2 activation in human thyrospheres [61]. Moreover, the metal dose may have bidirectional effects on ERK1/2 signaling, as documented for various metals [106,107]. Similar bidirectional effects may also depend on short-or long-term exposure to toxic metals [107], indicating that the final biological effect depends on the magnitude and duration of the exposure: the cell-metal interaction will cause either the predominance of detoxification and cell adaptive processes allowing (deregulated) survival or, when cell defenses are overwhelmed, may lead to cell death.…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 93%
“…Moreover, the metal dose may have bidirectional effects on ERK1/2 signaling, as documented for various metals [106,107]. Similar bidirectional effects may also depend on short-or long-term exposure to toxic metals [107], indicating that the final biological effect depends on the magnitude and duration of the exposure: the cell-metal interaction will cause either the predominance of detoxification and cell adaptive processes allowing (deregulated) survival or, when cell defenses are overwhelmed, may lead to cell death.…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 97%
“…Publication bias was evaluated by visually assessing the asymmetry of an inverted funnel plot, and then was supported quantitatively by Begg and Egger tests. [29,31]…”
Section: Methodsmentioning
confidence: 99%